Shakespeare for squirrels [large type] : a novel - Moore, Christopher, 1957- (Harper Large Print, an imprint of HarperCollinsPublishers, 2020)
In a mystery inspired by Shakespeare's most-performed play, Pocket of Dog Snogging assumes the duties of a murdered Puck to identify hidden adversaries who have complicated an arranged marriage.